Tracing adaptive reuse in the city for a situated know-how: A research study on Ankara as an archive of reused buildings (EAAE Annual Conference Proceedings, 2025)
Handbooks and atlases of adaptive reuse predominantly discuss and illustrate architectural examples in a case study format with a practice-focused ap- proach. However, examining reused buildings collectively rather than individu- ally prompts critical attention to what is already in the urban fabric and cultivates a care-based approach to built heritage in response to the changing face of an architectural practice focused more and more on transformation. Operating with a research-based approach, the course on traces, transformations and disappearances suggests digging into the city of Ankara as an experimental archive of adaptive reuse.Students are engaged in acts of tracing, mapping and indexing in order to form a collective archive of reused buildings by navigating through sites, archives, design practices, memories and ephemera. This research study situated in the very city that the students live in opens the possibility of experiencing ex- isting buildings in their post-reuse periods. It thus expands the understanding of adaptive reuse not as a design intervention but as a process by fostering a comprehensive assessment of sustainability.